Simulation modeling as a tool for the control of Foot-and-Mouth Disease (FMD) in endemic regions - Zaheer, Muhammad Usman, author; Rao, Sangeeta, advisor; Salman, Mo D., advisor; Steneroden, Katie, committee member; Weber, Steve, committee member; Magzamen, Sheryl, committee member (Colorado State University. Libraries, 2019)
To view the abstract, please see the full text of the document.
Keywords: endemic countries; foot-and-mouth disease; stochastic simulation; food security; animal health; spatially-explicit